2011
DOI: 10.15420/icr.2011.6.2.106
|View full text |Cite
|
Sign up to set email alerts
|

Improved Understanding of Stent Malapposition Using Virtual Bench Testing

Abstract: Intravascular imaging techniques such as optical coherence tomography (OCT) and intravascular ultrasound (IVUS) are often used to assess strut apposition, but only provide limited insight into the three-dimensional appositioning behaviour of stents. Recently, a new approach has been introduced to study the phenomenon of incomplete stent apposition (ISA) based on finite element simulations. In this study, we employed this virtual strut apposition assessment technique in the setting of coronary bifurcation stent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…With both stents, a large region with ISA is located immediately distally to the stenosis. Incomplete strut apposition is difficult to detect in vivo with current technology, including optical computer tomography, but can be straightforwardly assessed using computational simulations, as recently demonstrated by Mortier et al . In a clinical study on 107 CAS procedures, ISA has been reported in 11% of the arteries by intravascular ultrasound, and persisted after further balloon‐dilatation , suggesting that ISA often occurs in CAS but is not often detected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With both stents, a large region with ISA is located immediately distally to the stenosis. Incomplete strut apposition is difficult to detect in vivo with current technology, including optical computer tomography, but can be straightforwardly assessed using computational simulations, as recently demonstrated by Mortier et al . In a clinical study on 107 CAS procedures, ISA has been reported in 11% of the arteries by intravascular ultrasound, and persisted after further balloon‐dilatation , suggesting that ISA often occurs in CAS but is not often detected.…”
Section: Discussionmentioning
confidence: 99%
“…However, when a stent is deployed in a complex vessel domain, such as a bifurcation, incomplete stent apposition (ISA) necessarily occurs because of the limited stent flexibility. From the postimplantation geometry, the apposition of the stent struts onto the vessel wall was quantified as the local distance between the outer stent surface and the vessel endothelium, as recently proposed by Mortier et al . Using a fifth of the strut thickness (0.048 mm) as a threshold value of the stent‐to‐vessel distance to discriminate between apposition and malapposition, the ratio of malapposed area to PAA was computed to define the percentage of malapposed area (PMA).…”
Section: Methodsmentioning
confidence: 99%
“…However, clinical and pathophysiological implications of mechanical considerations should be further investigated in animal models or in a clinical setting. Even though previous experience in the finite element method and its validation (Mortier et al, 2011b) make us confident in the presented results, the lack of specific, experimental validation is one of the shortcomings of the manuscript. Other limitations of this work are model simplifications, such as the lack of realistic values for the wall thickness, which varies along the vasculature (Sommer et al, 2010).…”
Section: Discussionmentioning
confidence: 96%